A facile and scalable fabrication method for thin film composite reverse osmosis membranes: dual-layer slot coating. Issue 14 (22nd March 2017) - Park, Sung-Joon; Ahn, Won-Gi; Choi, Wansuk; Park, Sang-Hee; Lee, Jong Suk; Jung, Hyun Wook; Lee, Jung-Hyun
Abstract : The dual-layer slot coating technique can fabricate a sub-10 nm ultrathin, highly selective membrane outperforming commercial reverse osmosis membranes. Abstract : We report on a unique, facile and scalable fabrication technique, dual-layer slot coating (DSC) for high performance polyamide (PA) thin film composite (TFC) reverse osmosis (RO) membranes. DSC allows the simultaneous and continuous spreading of two reactive monomer solutions to create an unsupported PA layer via in situ polymerization, which is then adhered onto a porous support to form a membrane. DSC facilitates the characterization of the PA layer structure by easily isolating it. The DSC-assembled PA layer exhibits a thinner and smoother structure with a more wettable and less negatively charged surface than the one prepared via conventional interfacial polymerization (IP), which was attributed to the uniformly expedited amine (MPD) diffusion at the bulk liquid interface during film formation. As a result, DSC enables the formation of an extremely thin (∼9 nm) and dense PA layer using a very low MPD concentration, which is not feasible by conventional IP. Importantly, the DSC-assembled membrane shows an excellent water flux and NaCl rejection, exceeding both IP control and commercial RO membranes. The DSC technique will open a new paradigm for the fabrication of TFC membranes with strong commercial potential due to its simplicity, scalability and high performance.